2008
DOI: 10.1007/s12257-008-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of polyhydroxyalkanoates by Azotobacter vinelandii UWD using swine wastewater: Effect of supplementing glucose, yeast extract, and inorganic salts

Abstract: This study examined the effect of adding glucose, yeast extract, and inorganic salts to swine wastewater (SWW) in a batch culture on the production of a biodegradable plastic, polyhydroxyalkanoate (PHA). A bacterial strain, Azotobacter vinelandii UWD, was used to produce PHA without limiting the non-carbon nutrients. The addition of glucose (30 g/L) to the SWW medium increased the level of cell growth (4.4~7.0 times) and PHA production (3.8~8.5 times) depending upon the dilution of SWW. A 50% dilution of SWW w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…After incubation at 27ºC and 150 rpm, the growth of the isolate was monitored as previously mentioned and compared with growth on PDB (Ryu et al 2008, Chai et al 2009). …”
Section: Optimization Of Petrochemical Wastewater As Production Mediummentioning
confidence: 99%
“…After incubation at 27ºC and 150 rpm, the growth of the isolate was monitored as previously mentioned and compared with growth on PDB (Ryu et al 2008, Chai et al 2009). …”
Section: Optimization Of Petrochemical Wastewater As Production Mediummentioning
confidence: 99%
“…Overall, the amount of the polymer recovered at the end of fermentation was higher than that obtained in flasks, reaching amounts higher than 1 g/L of fermented R-NF. A similar experimental design for the optimization of the PHA synthesis through R-NF fermentation was carried out by the authors with a similar approach by using Azotobacter vinelandii UWD [ 79 ] as producer microorganism; nevertheless, the polymer production in any of the tested conditions, was lower than 127 ± 5 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…The molasses being an agro-industrial waste is cheapest and easily available substrate in Pakistan and may help to cut down the cost of PHA production. The production of PHA using organic wastes can be an environmental-friendly and economical alternative to using commercial feedstock (Ryu et al, 2008). Albuquerque et al (2007) reported that it has a very high sugar content (total sugars make up 54% w/w of the cane molasses), composed mainly of sucrose (62%), and fructose (38%).…”
Section: B Pfw1mentioning
confidence: 99%